Public policy beyond the financial crisis : an international comparative study - Haynes, Philip. (Routledge critical studies in public management ;, 2012)
"The economic crisis of 2008-2009 and beyond has provided the greatest challenge to public policy in the developed world since the Second World War, as the use of public monies to support banks and declining tax revenues have resulted in rising government borrowing and national debt. This book evaluates the failures of public policy in the half decade before the crisis, using the conceptual framework of complex systems. This analysis reveals the fundamental failings of globalization and the lack of a robust and resilient public sector paradigm to assist countries in economic recovery. The research has benefited from UK Economic and Social Research Council (ESRC) funding for a Knowledge Exchange that applied the most relevant and applied aspects of complex systems theory to contemporary policy problems. Innovative statistical methods are used to profile and group countries both before and after the 2008-09 crisis. This shows the countries that are best prepared for the ongoing and prolonged Euro zone crisis of 2010-12. The book proposes a new model of public policy that asserts itself over the paradigm of market liberalism and places the public values of full employment, sustainability and equality at the top of the post crisis policy agenda"--